Characterization of m6A-related lncRNA signature in neuroblastoma - Li, Liming; Chen, Sisi; Li, Jianhong; Rong, Guochou; Yang, Juchao; Li, Yunquan (Frontiers in Pediatrics, 2022)
N6-methyladenosine (m6A) is one of the most common modifications in mRNA, rRNA, tRNA, microRNA and long-chain non-coding RNA. The effect of m6A on the stability of RNA depends on m6A "Readers", "Writer" and "Erase". In this study, we identified a set of m6A-related genomic expression profiles in Neuroblastoma(NBL) based on Therapeutically Applicable Research To Generate Effective Treatments (TARGET：https://ocg.cancer.gov/programs/target). We identified two subgroups of Neuroblastoma (High-risk group and Low-risk group) by applying consensus clustering to m6A RNA methylation regulators. Compared with the Low-risk group, the High-risk group correlates with a poorer prognosis. Moreover, the present study also revealed that the high-risk group are significantly enriched in the tumor-related signaling pathways, including P53 signaling pathway, cell cycle and DNA repair. This finding indicates that these molecular prognostic markers may also be potentially valuable in early diagnosis, which provides a new research direction to study the molecular mechanisms underlying the development of NBL. In colussion, the study constructed a new model of NBL prognosis based on m6a-associated lncRNAs. This model is helpful for stratification of prognosis and development of treatment strategies